Riwayat Hidup Nabi Muhammad S.A.W - Andini Nabila; Bimo Utomo Putro; Dela Yulianti; M.Aditya Fauzan; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
The Prophet Muhammad taught people about the Islamic religion and spread his message to humanity. He was not only a religious leader but also a leader for the entire community and country. He helped build mosques and encouraged people to befriend others who believed in Islam. His greatest success was becoming the leader of the country and spreading Islam to various parts of the world. He also made a special agreement called the Medina Charter, which showed that he cared about everyone, including Muslims and Jews, and wanted them to live together peacefully. The Prophet Muhammad also brought different tribes together and made them friends, not enemies.